Occupational safety and health (OSH) knowledge, practices and injury patterns among solvent manufacturing workers: a cross-sectional study - Ali, Nina Fatma; Zulkaple, Radhiah (Universiti Putra Malaysia, 2024)
Introduction: Adequate knowledge and practice of Occupational Safety and Health (OSH) is essential to reduce workplace injuries. This cross-sectional study aims to examine the relationship between sociodemographic factors and the level of knowledge, practice, and injury patterns related to OSH among workers in a solvent manufacturing factory. Methods: Purposive sampling was used to select 286 respondents who were given validated self-administered questionnaires through WhatsApp and paper. Secondary data on workplace injuries were also collected between December 2021 and October 2022. The collected data was then analyzed using SPSS Version 27. Results: The majority of the workers exhibited good knowledge levels of OSH at their workplace, with all workers showing moderate to good levels of OSH practices. There was no significant association between gender, age, education level, and work experience with the level of OSH knowledge. However, significant associations were observed between gender and age with the level of OSH practices with p = <0.001 for both factors, while no significant association was found between working experience and education level with the level of OSH practices. Moreover, the study found no significant association between knowledge and practice, knowledge and injury, as well as practice and injury. Over 11 months, three incidents were reported, with acute injuries caused by chemical hazards and physical risks. Workers also reported issues related to the enforcement of Personal Protective Equipment (PPE), ergonomic problems, environmental factors, and the condition of their workstations. Conclusion: The study highlights the need for safety and health training to improve the workers’ OSH practices and reduce the incidence of workplace injuries in the manufacturing factory.